Montaje: hacia un tratamiento perceptivo de los mensajes audiovisuales - Morales Morante, Luis Fernando (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2009)
The communicative effect of editing is often associated with technical factors, the precision of cuts and the connections by which the director of a film ordered a chain of elements with the aim to give voice to a certain discourse. However, its effectiveness is based upon perceptual keys which are meant to catch the attention of the viewer and which facilitate the recognition and interpretation of some relevant audiovisual features. This article reflects on the elements that compose this relationship and on their potential to improve the expressive capacities of the filmic discourses. It proposes a cinematographic processing model, based upon the configuration of physical attributes and on the significant hegemony of the communicative fusion of image and sound.